Prognostic value of serum S100B concentration in patients with acute spontaneous supratentorial intracerebral hemorrhage - О. A. Koziolkin; A. A. Kuznietsov (Patologìâ)
Aim of the work – to evaluate the informativeness of serum protein S100B levels in detection of short-term prognosis in patients with acute period of spontaneous supratentorial intracerebral hemorrhage (SSICH) on the background of concervative therapy.